Analisis Standar Belanja (ASB) Pada Pemerintah Kabupaten Padang Pariaman - Djefris, Dedy; Rosalina, Eka; Rasyidah, Rasyidah; Wirahadi Ahmad, Afridian; Misra, Fauzan (Akuntansi dan Manajemen, 2021)
In general, regional financial management goes through the following stages: budget preparation, activity implementation and financial accountability or financial report preparation. Based on the above, Permendagri No. 21 of 2011 concerning Guidelines for Regional Financial Management, states the need for Standard Expenditure Analysis (ASB) as a main research tool in conducting performance-based budgeting. Expenditure Standard Analysis (ASB) is an assessment of the fairness of the costs and workloads used to carry out an activity at each Regional Apparatus Organization (OPD). This study aims to determine the reasonableness of spending in carrying out an activity so as to minimize unclear expenses that cause budget inefficiency. This research was conducted at the Regional Government of Padang Pariaman Regency, West Sumatra. The stages of preparing this Standard Expenditure Analysis (ASB) are to input data and group similar data, determine the Cost Driver, create regression equations, determine the average, upper and lower limits, and analyze the fairness of costs and workloads of the ASB model. has been compiled. The preparation of a Standard Expenditure Analysis (ASB) at the District Government of Padang Pariaman which is discussed in this is for the types of training activities for personnel and training for the community.